Experience of Nurses in Caring for Patients with Dementia During Acute Conditions and Pain Management - Kairiūnienė, Erika; Valiulienė, Žaneta; Stalnionienė, Loreta (Slauga. Mokslas ir praktika, 2024)
Nursing care for patients with dementia is complex, as dementia is a clinical syndrome primarily characterized by cognitive impairment. All patients are unique individuals, but due to their condition, they share similar needs that must be identified and met. The experience of nursing patients with dementia is challenging and difficult, particularly due to acute conditions and pain management. The aim of the study is to reveal the experiences of nurses in caring for patients with dementia during acute conditions and pain management. The research problem encompasses the following main questions: what difficulties and challenges do nurses face when caring for patients with dementia; what is the nursing experience in caring for patients with dementia during acute conditions and in pain management? A qualitative study was conducted in the palliative care and nursing department of Hospital X, using the interview method. Nurses caring for patients with dementia encounter various difficulties: managing pain and acute conditions, sudden changes in patients’ health status, comprehensive patient care, and a lack of patience. The main challenges are the complex nursing process, acute conditions, patient behavior problems, pain management, communication with patients’ relatives, providing psychological support to patients, personal factors (lack of patience and time), and organizational factors (staff shortages, heavy workloads). Acute conditions are managed by assessing the situation and monitoring patients according to doctors’ orders. Recognizing and medicating pain as needed is crucial for pain management. Various problems arise in caring for patients with dementia, the most common of which occur in communicating with the patient’s relatives, due to heavy workloads, and a lack of information in providing person-centered care. These problems are most often resolved through communication with colleagues and independent learning to search for necessary or missing information.
Keywords: dementia; nursing care for patients with dementia; nursing problems